Online Communities - Zaphiris, Panayiotis; Ang, Chee Siang; Laghos, Andrew (My University, 2007)
Preece et al. examine the nature of social interaction in online communities and address sociability and usability in this context. The chapter is quite useful for those interested in understanding online communities, how to promote social interaction because it considers the topic from a broad set of allied areas and discusses methods and frameworks used for analysis and support of social interaction. Of particular interest is the discussion regarding what is an online community and the approach taken from various disciplines. The practical focus of the chapter and its discussion on developing and evaluating online communities is also particularly useful for those interested in building and evaluating technologies that support successful online communities. This chapters many useful implications pertain to my areas of interest: in particular, extending Viegass (2004) notion of online community and cooperation by using arguments found in this chapter.